A Prospective Observational Study on the Effects of XingQi HuoXue Decoction on Gut Microbiota and Clinical Outcomes in Sepsis Patients with Acute Gastrointestinal Injury - Zhang J; Zhi Y; Xia G; Feng D; Lei S (Infection and Drug Resistance)
Jiaying Zhang,* Yihui Zhi,* Guolian Xia,* Dandan Feng, Shu Lei The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Hangzhou, Zhejiang, 310006, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shu Lei, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Hangzhou, Zhejiang, 310006, People’s Republic of China, Email 13588132236@163.comBackground: Therapeutic options for sepsis-associated acute gastrointestinal injury (AGI) remain limited. In this study, we explored the potential of a decoction called XingQiHuoXue (XQHX), which was formulated by us, in patients with septic AGI.Materials and Methods: It was a non-randomized observational study. Forty-nine patients diagnosed with septic AGI classified as qi stagnation and blood stasis syndrome (QSBSS), a condition characterized by unsmooth flow of qi and blood, were enrolled. The patients were divided into the treatment group (routine treatment and the XQHX) and the control group (routine treatment). Clinical characteristics encompassed demographics, underlying diseases, disease severity and prognostic outcomes. Gut microbiota data were derived from characterization of pre- and post-treatment fecal specimens collected from 15 patients enrolled. The clinical and gut microbiota characteristics were compared between the two groups.Results: Among the 49 patients, 30 showed improvement, including 19 patients from the treatment group and 11 from the control group. The difference in the improvement rate between the groups was significant (P < 0.05). With regard to changes in the microbiome composition, the treatment group showed a significant decrease in the abundance of Bacteroides, and Enterobacteriaceae/g- (q = 0.04 and q = 0.006), accompanied by a significant increase in the abundance of Enterococcus (q = 0.01). These changes were not found in the control group. The abundance of Bacteroides and Enterobacteriaceae/g- was positively correlated with the Acute Physiology and Chronic Health Evaluation II and Sequential Organ Failure Assessment score (R = 0.778 and 0.499), while the abundance of Enterococcus showed a negative correlation with the score (R = − 0.811 and − 0.656).Conclusion: Our preliminary findings suggest that XQHX may improve the prognosis of patients with septic AGI and QSBSS. The milder disease presentation and better prognosis could be associated with alterations in the gut microbiota induced by XQHX.Keywords: sepsis, acute gastrointestinal injury, traditional Chinese medicine, gut microbiota